2020
DOI: 10.1177/2048004019900748
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-mediated inflammation and cardiovascular risk factors in type 2 diabetes mellitus: A systematic review and meta-analysis of pre-clinical and clinical studies

Abstract: Background: Monocyte-mediated inflammation increases the risk of developing type 2 diabetes mellitus and cardiovascular disease. This is the first systematic review and meta-analysis of studies reporting on monocyte-mediated inflammation in type 2 diabetes mellitus. Methods: This systematic review and meta-analysis was registered in the international prospective register of a systematic review: CRD42019132902. The MEDLINE, EMBASE and Google scholar electronic databases were searched, and a random-effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(150 reference statements)
0
12
0
Order By: Relevance
“…This is an essential result since tenacious hyperglycemia, seen in T1D, is already known to mediate iNOS induction, leading to the activation of protein kinase enzymes such as PKC/c-Jun N-terminal kinases (JNKs)/mitogen-activated protein kinase (MAPK) to propagate the detrimental effects of inflammation ( Giacco and Brownlee, 2010 ). Notably, activation of such pro-inflammatory mechanisms can directly cause excess generation of oxidation products that precede the onset of atherosclerosis and endothelial dysfunction, which are major risk factors for the development of cardiovascular diseases ( Rose et al, 2010 ; Mokgalaboni et al, 2020 ). Although there was limited information on its cardioprotective effects, much evidence suggests Moringa oleifera extracts can significantly decrease pro-inflammatory and apoptotic markers such as TNF-α, IL-1β, IL-6, NF-κβ, caspase 3, caspase 9, and tumor protein (p53) to alleviate the detrimental effects of hyperglycemia in preclinical models of T1D ( Muhammad et al, 2016 ; Omodanisi et al, 2017a ; Azevedo et al, 2018 ; Oguntibeju, 2019 ).…”
Section: Moringa Oleifera Extracts Improve Markers Of Oxidat...mentioning
confidence: 99%
“…This is an essential result since tenacious hyperglycemia, seen in T1D, is already known to mediate iNOS induction, leading to the activation of protein kinase enzymes such as PKC/c-Jun N-terminal kinases (JNKs)/mitogen-activated protein kinase (MAPK) to propagate the detrimental effects of inflammation ( Giacco and Brownlee, 2010 ). Notably, activation of such pro-inflammatory mechanisms can directly cause excess generation of oxidation products that precede the onset of atherosclerosis and endothelial dysfunction, which are major risk factors for the development of cardiovascular diseases ( Rose et al, 2010 ; Mokgalaboni et al, 2020 ). Although there was limited information on its cardioprotective effects, much evidence suggests Moringa oleifera extracts can significantly decrease pro-inflammatory and apoptotic markers such as TNF-α, IL-1β, IL-6, NF-κβ, caspase 3, caspase 9, and tumor protein (p53) to alleviate the detrimental effects of hyperglycemia in preclinical models of T1D ( Muhammad et al, 2016 ; Omodanisi et al, 2017a ; Azevedo et al, 2018 ; Oguntibeju, 2019 ).…”
Section: Moringa Oleifera Extracts Improve Markers Of Oxidat...mentioning
confidence: 99%
“…Factors released by the adipose tissue such as pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-1b), non-esterified fatty acids, glycerol, and hormones may underly insulin resistance [ 115 ]. The disbalance of the immune system, the endothelial activation of monocytes, and macrophages in the adipose tissue may also release TNF-α and IL-6, thus exacerbating inflammation [ 116 , 117 ]. A meta-analysis of 20 clinical trials with 1065 T2DM patients versus 1103 healthy controls showed a correlation with monocyte activation and CVD risk in T2DM [ 116 ].…”
Section: Clinical Complications Of T2dmmentioning
confidence: 99%
“…The disbalance of the immune system, the endothelial activation of monocytes, and macrophages in the adipose tissue may also release TNF-α and IL-6, thus exacerbating inflammation [ 116 , 117 ]. A meta-analysis of 20 clinical trials with 1065 T2DM patients versus 1103 healthy controls showed a correlation with monocyte activation and CVD risk in T2DM [ 116 ]. Obesity management with special diet, exercises resulting in at least 15% weight loss, and longer sleep may have great disease-modifying effect on T2DM [ 118 , 119 ].…”
Section: Clinical Complications Of T2dmmentioning
confidence: 99%
“…Chronic inflammation and the persistent activation of peripheral monocytes and neutrophils are associated with the pathogenesis of type 2 diabetes mellitus (T2DM). Activated monocytes can further initiate atherosclerosis and increase the risk of complications in people living with T2DM [ [1] , [2] , [3] ]. For example, the monocyte chemoattractant protein 1 (MCP-1) plays a pivotal role in the recruitment of monocytes in response to atherogenic stimuli such as hyperglycaemia and dyslipidaemia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%